Current management strategies and long‐term clinical outcomes of upper extremity venous thrombosis. (4th April 2016) - Bleker, S. M.; van Es, N.; Kleinjan, A.; Büller, H. R.; Kamphuisen, P. W.; Aggarwal, A.; Beyer‐Westendorf, J.; Camporese, G.; Cosmi, B.; Gary, T.; Ghirarduzzi, A.; Kaasjager, K.; et al.
Abstract : Essentials Few data exist on outcome of upper extremity deep and superficial vein thrombosis (UEDVT and UESVT). We followed 102 and 55 patients with UEDVT or UESVT, respectively, for a median of 3.5 years. Risk of recurrent venous thromboembolism was low in both diseases, and the mortality high. Postthrombotic symptoms were infrequent and cancer patients had a higher risk of recurrent VTE. Summary: Background: There is scant information on the optimal management and clinical outcome of deep and superficial vein thrombosis of the upper extremity (UEDVT and UESVT). Objectives: To explore treatment strategies and the incidence of recurrent venous thromboembolism (VTE), mortality, postthrombotic symptoms, and bleeding in patients with UEDVT and UESVT and to assess the prognosis of cancer patients with UEDVT. Patients/methods: Follow‐up of patients with UEDVT or UESVT, who were enrolled previously in a diagnostic management study. Results: We followed 102 and 55 patients with UEDVT and UESVT, respectively, both for a median of 3.5 years. Anticoagulant treatment was started in 100 patients with UEDVT (98%) and in 40 (73%) with UESVT. Nine patients with UEDVT (9%) developed recurrent VTE, 26 (26%) died, 6 (8%) of 72 patients had moderate postthrombotic symptoms, and 5 (5%) experienced major bleeding. One patient with UESVT had a recurrent VTE, 18 (33%) died, none had moderate postthrombotic symptoms, and none had major bleeding. Of the cancer patients with UEDVT, 18% had recurrent VTE vs. 7.5% in non‐cancer patients (adjusted hazard ratio 2.2, 95%CI 0.6–8.2). The survival rate was 50% in cancer patients with UEDVT vs. 60% in those without (adjusted HR 0.8, 95%CI 0.4–1.4). Conclusions: The risk of recurrent VTE was low in patients with UEDVT, and negligible for UESVT. Mortality was high for both diseases. Postthrombotic symptoms were infrequent and mild. Anticoagulant therapy of UEDVT carried a substantial risk of major bleeding. Cancer patients had a significant risk of recurrent VTE.